Effect of Thermal Aging on Color Stability and Mechanical Properties of High-Density CAD/CAM Polymers Utilized for Provisional Restorations - Rasha Alharthi; Ali Robaian Alqahtani; Abdullah Mohammed Alshehri; Abdulrahman Almalki; Heba Wageh Abozaed; Eman Mohamed Raffat Hussein; Tarek Ahmed Soliman (Journal of Functional Biomaterials)
Background: This study evaluated and compared the effects of thermal aging on the color stability and mechanical properties of CAD/CAM polymers utilized for provisional restorations. Material and Methods: Three CAD/CAM polymers in this study: CAD-Temp (CAT), Everest C-Temp (CT), and PEEK (PK). Forty specimens of each material were randomly assigned to two subgroups. Subgroup A was immersed in distilled water for 24 h, whereas Subgroup B was subjected to 5000 thermal cycles. The color stability, flexural strength (FS), survival probability, and microstructures were evaluated following thermal cycling. Data analysis was conducted utilizing two-way ANOVA along with Tukey’s test. Results: The CAT (3.74 ± 0.39) and CT (3.51 ± 0.54) groups exhibited the highest color variations, while PEEK (2.95 ± 0.45) showed the lowest color change. The baseline groups showed that the CT group had the highest flexural strength value (p < 0.05). The flexural strength values of CAT and CT groups significantly decreased (p < 0.05) following thermal cycling. No significant decrease in FS was observed following thermal cycling in the Pk group (p = 0.16). Conclusions: The color measurement and flexural strength outcomes were significantly influenced by CAD/CAM materials and thermal cycling. The CT group demonstrated superior flexural strength compared to the other groups, both before and after thermal cycling. The PK group shows the lowest color change compared to other groups. Regardless of aging condition, C-Temp and PEEK materials recorded the highest survival probability, a 95% significance level compared to CAD-Temp.